AN INVESTIGATION ON THE PROBLEMS EXPERIENCED IN INCLUSIVE EDUCATION IN PRIMARY SCHOOLS - YÜCEL , Şaban; ŞEN , İbrahim (SSD Journal, 2022)
Inclusive education is an application that is carried out in our country with some problems. Individual differences are a factor that is taken into account in our education system and given importance for every student within the principle of equality.Inclusive students' getting the highest benefit from the education process will produce positive results both for themselves and for other students. The aim of this research is to examine the problems experienced in inclusive education applied in primary schools and to determine the solution proposals. In this context, a qualitative research was conducted by conducting interviews with 5 experienced classroom teachers using a semi-structured form. As a result of the research findings, three sub-themes were formed, grouped under two themes, academic, social and psychological titles, as the problems experienced in inclusive education and solution suggestions for the problems experienced in inclusive education. While the most common answers to the problems experienced by mainstreaming students were learning difficulties, embarrassment, exclusion and lack of self-confidence, the most common answers to the solution suggestions were raising awareness of teachers, empathy, effective follow-up of the guidance service and educating families. By discussing the research findings, suggestions for school administrators, teachers and researchers were presented.